Pendampingan AKM Kelas pada Sekolah Dasar Kelas V SDN Bandorasakulon 3 Kecamatan Cilimus Kabupaten Kuningan - Suseno, Endra; Erik Kurniadi; Ragel Trisudarmo (Journal of Innovation and Sustainable Empowerment, 2023)
The low ability of students in literacy and numeracy underlies the training on the application of the AKM application to students, in an effort to equip skills in terms of working on minimum competency assessments. These knowledge and skills can be used as capital in the work of assessing the minimum competency of students which can be used as ICT-based learning media. With this training as a learning medium, it is hoped that it can increase the knowledge and skills of students. Students can better understand what will be done during the implementation of the minimum competency assessment, especially things of a technical nature. This training can also provide provisions for our students about the use of this application which is a plus, where students can use it as a learning tool and a means of developing knowledge, especially in the field of using minimum competency assessment applications.